Changes in the Foveal Outer Nuclear Layer of Central Serous Chorioretinopathy Patients Over the Disease Course and Their Response to Photodynamic Therapy - Deng, Kaixin; Gui, Yufei; Cai, Yi; Liang, Zhiqiao; Shi, Xuan; Sun, Yaoyao; Zhao, Mingwei (Frontiers in Medicine, 2022)
Objective: To investigate the association between foveal outer nuclear layer (ONL) thickness and the natural course of central serous chorioretinopathy (CSC), as well as the thickness change after photodynamic therapy (PDT), exploring the PDT timing for CSC. Methods: This retrospective consecutive case series included 358 CSC patients between January 2014 and December 2019. All patients were divided into four groups depending on disease duration: Group A: ≤1 month; Group B: >1 and ≤3 months; Group C: >3 and≤6 months and Group D: >6 months. Foveal ONL thickness of the CSC eye and the clinically healthy fellow eye were measured and compared in all patients. Fifty-six patients were successfully treated with half-dose of PDT, showing complete subretinal fluid absorption, were followed up for more than 6 months and further investigated. The recovery of foveal ONL thickness was analyzed in the affected eyes of patients with different disease duration. Results: No significant reduction was found in CSC foveal ONL thickness (μm) compared to the fellow eye in patients with disease duration less than 1 week (112.3 ± 12.2 vs. 116.7 ± 15.3, P = 0.268). Patients with longer disease duration had varying degrees of ONL thinning compared to the contralateral eye (all P < 0.05) and this difference was more pronounced in patients with disease duration greater than 6 months (75.8 ± 12.9 vs. 113.0 ± 11.5, P < 0.001). At 6-month follow-up after PDT, foveal ONL thickness of patients with <1 month disease duration recovered significantly from onset (97.3 ± 18.2 to 113.6 ± 8.7, P < 0.001) and became similar to that of the healthy fellow eye. Foveal ONL thickness of patients with duration>1 and≤3 months recovered significantly (88.5 ± 11.5 to 95.8 ± 11.3, P = 0.012) but remained thinner than that of the healthy fellow eye. Foveal ONL thickness did not improve significantly in cases with disease duration longer than 3 months (P > 0.05). Conclusion: Foveal ONL thinning was positively associated with disease duration prior to treatment suggesting that longer disease duration limits scope for foveal ONL recovery. CSC patients should be treated with PDT as soon as possible to prevent disease development and reduced visual function.